Individual Differences in Executive Functioning and Their Relationship to Emotional Processes and Responses. (April 2015) - Schmeichel, Brandon J.; Tang, David
The executive functions (including response inhibition, memory updating, and task switching) appear to form the core of higher-order cognitive processes in humans. Relatively little research has been devoted to the role of the executive functions in emotional and motivational processes. The current article surveys evidence on the contributions of individual differences in executive functioning to emotion and emotion regulation in adults. The findings reveal that cognitive ability helps to shape human emotional life and raise new questions about how and why this is so.